Fashioning adultery: Gender, sex, and civility in England, 1660-1740 - Turner, David M (Cambridge University, 2013)
This book provides the first major survey of representations of adultery in later seventeenth- and early eighteenth-century England. Bringing together a wide variety of literary and legal sources it charts and explains crucial shifts in perceptions of marital infidelity and the development of a more rational understanding of adultery.